Optimalisasi Pemanfaatan Google Dokumen dalam Melatih Keterampilan Menulis Surat Resmi Peserta Didik - Tamsiruddin, (Jurnal Didaktika Pendidikan Dasar, 2025)
Optimizing the use of technology in learning, for example, the use of Google documents, is one effort to create liberating learning because this learning is more contextual and contemporary. This research aims to examine and describe the optimization of the use of Google documents in training official letter writing skills for students in class VII.1 UPTD SMP Negeri 1 Parepare. This research uses a descriptive method, namely describing the process and results of learning to write official letters by optimizing the use of Google documents. The subjects in this research were 30 students in class VII.1 UPTD of SMP Negeri 1 Parepare, 13 men and 17 women. The results of the research show that the use of Google Documents features makes students in class VII.1 UPTD SMP Negeri 1 Parepare more actively involved in learning and skilled at writing official letters, with an average score of 78.67, which is in the good category. Judging from the assessment aspect of official letter writing skills, students' ability to present the content and structure of an official letter is in the very good category; their ability to choose words and present visualizations of an official letter digitally is in the good category; and their ability to use spelling (capital letters and punctuation) is in the very poor category or needs intervention.